Analysis Of The Islamic Bank Cash Withdrawal Service System For Foreign Tourists (A Case In Aceh Tengah Indonesia) - Tiaranita, Dinda; Djakfar, Inayatillah; Mulia, Rika (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2024)
Aceh Tengah is highland that attracts many tourists from domestic or foreign countries in Aceh. Bank Syariah Indonesia (BSI) of the Islamic banks that plays an important role regarding the cash withdrawal process by foreign tourists in Aceh Tengah District, Aceh Province, Indonesia. The study aims to determine how BSI facilitates cash withdrawal services in Aceh Tengah. This study used a qualitative method with a descriptive field approach from foreign tourists that visiting Aceh Tengah. The results of this study indicate that there are several obstacles experienced by tourists in the cash withdrawal process, such as some of their bank cards are not supported by the available ATM (Automated Teller Machine) even through the Teller counters would have been not accessible for them. It is expected that this study will highlights the needs of upgrading system for Islamic banks that operating in Aceh Tengah for foreign tourists in using cash withdrawal services.